TRACKING INDEPENDENTLY INDONESIA ISLAMIC HISTORIOGRAPHY - Fatiyah, Fatiyah; Hariyanto, Bambang (Universitas Islam Negeri Alauddin Makassar, 2016)
Muslims as the majority in Indonesia has not contributed properly in the writing of the Indonesian National History. The role of Moslems covered by the hegemony of national historiography, even in the previous era. It must be admitted that Islam has played an important role in the Indonesia's archipelago and national history. Islam once became a super political force by the existence of Islamic kingdoms in various islands of the archipelago. In the modern era, Islam has transformed into a reckoned political force. However, in reality, the discussion about this issue cannot be found. Therefore, the authors apply independent approach to study Indonesian Islamic historiography that focusing on Indonesia Muslims literary culture and its periodization. Writing process of historiography in each area would give a birth to new various perspectives. Indonesia's post-colonial historiography carries a heavy burden in the writing process of Indonesia's struggle realities for independence at that time. The emergence of Indonesia center perspective was unable to complete the historiography mission. Moreover, the historiography has deteriorated the Muslims’ roles in the nation struggles. This claim is proven after Sejarah Umat Islam (History of Muslims) book is published. The book does not depict any roles of Indonesia Muslims except their political power. Furthermore, when the book discusses religious aspects, it only offers sections about Islamic kingdoms, pesantren and Kyais; as if there are no other interesting issues related to Indonesia Muslims.